2003
DOI: 10.1053/ejvs.2002.1849
|View full text |Cite
|
Sign up to set email alerts
|

Graft patency and clinical outcome of femorodistal arterial reconstruction in diabetic and non-diabetic patients: Results of a multicentre comparative analysis

Abstract: our preliminary results support the view that infrainguinal bypass grafting can be safely done even in diabetics. Despite increased mortality in this group, liberal indication for reconstructive vascular surgery seems to be justified by favourable patency rates and clinical outcome in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
63
2
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 17 publications
(8 reference statements)
7
63
2
7
Order By: Relevance
“…Considered together,these may suggest poorer outcome in treated patients or,even worse, may completely discourage any aggressive vascular surgical treatment in these patients (22). however, despite decreased surdespite decreased survival among diabetics (19,23,24) therei se vidence that bypass grafting to the leg is worthwhile (19)(20)(21)(22)(23)(24). In anation-wide analysis of diabetes as arisk factor for postoperative major mortality and morbidity after surgery for CLI in Finland during 1991-1999, diabetes was found to be an independent risk factor for postoperative BK amputation (37).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considered together,these may suggest poorer outcome in treated patients or,even worse, may completely discourage any aggressive vascular surgical treatment in these patients (22). however, despite decreased surdespite decreased survival among diabetics (19,23,24) therei se vidence that bypass grafting to the leg is worthwhile (19)(20)(21)(22)(23)(24). In anation-wide analysis of diabetes as arisk factor for postoperative major mortality and morbidity after surgery for CLI in Finland during 1991-1999, diabetes was found to be an independent risk factor for postoperative BK amputation (37).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown an inverse correlation between the incidence of infrainguinal bypass reconstruction and that of amputation (5, [14][15][16][17][18]. Equal patency and limb salvage rates after infrainguinal revascularization for diabetic and nondiabetic patients have been reported (19)(20)(21)(22)(23)(24). Furthermore, implementation of am ultidisciplinary team implementationo fam ultidisciplinary team approach for prevention and treatment of diabetic foot ulcers has reported to be effective means of preventing amputations (25)(26)(27)(28)(29)(30)(31).…”
mentioning
confidence: 99%
“…72,74,75 As diabetics have a pattern of disease that includes a heavy burden of disease in tibioperoneal arteries, the level of distal anastomosis has proved to be a much weaker predictor of graft failure than conduit quality.…”
Section: Tibial-pedal Diseasementioning
confidence: 99%
“…Es, por tanto, una enfermedad subestimada y subdiagnosticada [5][6][7] . Los factores de riesgo relacionados con su desarrollo son clásicamente, la hipertensión arterial (HTA), el tabaquismo, la diabetes y la hipercolesterolemia 7,8 . Sin embargo, existen diferencias en la prevalencia de estos factores de riesgo según el territorio vascular analizado.…”
Section: Introductionunclassified